Walnut: past and future of genetic improvement - Bernard, Anthony; Lheureux, Fabrice; Dirlewanger, Elisabeth (Tree genetics & genomes, 2018)
Persian or English walnut ( Juglans regia L.), the walnut species cultivated for nut production, is one of the oldest food sources known. Persian walnuts, native to the mountain valleys of Central Asia, are grown worldwide in temperate areas. World production exceeds three million tons since 2012, mostly provided by China, the USA, and Iran. Despite very ancient culture of walnut species ( Juglans spp.), breeding actually started in the twentieth century. Using a range of methodologies, from morphological markers to the most recent advances in genome analysis, many genetic studies of walnut have been conducted during the past 30 years, including examination of diversity, determination of relationships within or among germplasm collections and populations, phylogenetic and origin elucidation, genetic map construction, and biotic or abiotic stress investigations. The genetic improvement of walnut has undergone great evolution. The producing countries of the Middle East have widely studied morphological characteristics of walnut. The USA and France, for example, are behind important cultivar releases such as “Chandler” and “Franquette.” Finally, genomics represents a major breakthrough in walnut improvement, in particular by recent sequencing of both chloroplast and nuclear genomes. This review summarizes worldwide molecular and “omics” studies and gives an overview of the main walnut breeding programs.